2022
DOI: 10.3390/ijerph19159345
|View full text |Cite
|
Sign up to set email alerts
|

Low Interleukin-12 Levels concerning Severe Malaria: A Systematic Review and Meta-Analysis

Abstract: Although many studies have investigated the role of interleukin (IL)-12 cytokine in the pathogenesis of severe malaria, these studies were based on a limited number of participants, possibly affecting their outcomes. We analyzed the difference in IL-12 levels between patients with severe and uncomplicated malaria through a meta-analysis. A systematic review was conducted following the Cochrane Handbook for Systematic Reviews of Interventions and was reported according to the Preferred Reporting Items for Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The publication bias was assessed by visualizing funnel plot symmetry. The funnel plot would be asymmetric in case of publication bias [ 24 , 25 ]. Egger’s test was used to assess funnel plot symmetry [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publication bias was assessed by visualizing funnel plot symmetry. The funnel plot would be asymmetric in case of publication bias [ 24 , 25 ]. Egger’s test was used to assess funnel plot symmetry [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The funnel plot would be asymmetric in case of publication bias [ 24 , 25 ]. Egger’s test was used to assess funnel plot symmetry [ 25 ]. Egger’s test with statistical significance ( p < 0.05) might indicate that funnel plot asymmetry was due to a small-study effect [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Future studies might be successful in focusing on employing immunogenic vaccine candidates that are expressed in the infective (sporozoite) stage of C. felis infection in order to initiate an expedited immune response against infection (before C. felis reaches the highly proliferative schizogenous phase). Studies have also shown that IL-12 is linked to long-lasting cellular immunity against intracellular parasites [ 67 , 68 , 69 , 70 ]. Development of vaccines that can result in persistent IL-12 could be an attractive strategy to enhance the efficacy of vaccines against C. felis .…”
Section: Discussionmentioning
confidence: 99%